BODIPY-phenylacetylene macrocycle motifs for enhanced light-harvesting and energy transfer applications1. Issue 71 (2nd August 2015) - Yousaf, M.; Lough, A. J.; Schott, E.; Koivisto, B. D.
<x xml:space="preserve">Abstract</x> BODIPY-phenylacetylene macrocyclic hybrids are reported, where energy transfer is observed from the phenylacetylene unit to the BODIPY core.